Evaluating nutritional and behavioral health and vegetable cultivars as part of a Native American gardening project - Galgamuwe Arachchige, Pabodha Galgamuwa (Kansas State University, 2013)
Due to health and nutritional disparities, prevalence of obesity and related diseases among American Indians is found to be higher than the U.S. general population. To promote a healthy lifestyle, the long term goal of this project is to increase fresh fruit and vegetable availability through gardening for the Prairie Band Potawatomi Nation (PBPN) tribe in Kansas. In achieving this ultimate goal, two studies were conducted with the objectives of: 1) Evaluate the nutritional and behavioral health indicators for the residential population of the tribe and identify key constraints of gardening activity in the reservation; and 2) Conduct vegetable cultivar trials comparing different open pollinated (OP) and hybrid cultivars of tomato (Lycopersicon lycopersicum), pepper (Capsicum annum) and eggplant (Solanum melongena var. esculentum) to identify best yielding cultivars. Three surveys were conducted to assess the residential population with respect to gardening activity, fruit and vegetable consumption, health status, physical activity and socioeconomic status, using convenience samples. Cultivar trials comparing 6 pepper, 3 eggplant, and 5 tomato cultivars were conducted in 2012 and 2013 growing seasons. PBPN respondent group revealed significant health disparities compared to the general U.S. and Kansas populations. A higher proportion of this group was in poverty which had strong correlations with land ownership, gardening experience, and attendance to gardening workshops. “No knowledge” and “no space” were identified as key gardening constraints. Hybrid Jetstar was the best tomato cultivar identified, while Cherokee Purple was the best yielding OP cultivar. No difference in performance was observed among the three eggplant cultivars tested. Sweet pepper hybrids Flamingo and Alliance outperformed OP California Wonder which was moderate in production. OP chili pepper cultivars Anaheim 118 and hybrid Chili G76 outperformed hybrid Charger. Identified best yielding cultivars could be distributed among tribal members to support in-place gardening initiatives. Gardening limitations of “no land” and “no knowledge” could be mitigated by increasing participation at the community garden and attendance for gardening workshops. Strategic approaches should be implemented to attract people in poverty to engage in gardening and increase gardening activity in the reservation for nutritional, health and economic benefits.
Keywords: Potawatomi; Diet; Tribal; Socioeconomic; Horticulture (0471); Native American Studies (0740); Social Research (0344)